Invasion of Patches of Natural Vegetation by Exotic Woody Species in Obafemi Awolowo University, Ile Ife - Akinwande, Ayomiposi Olayinka (2015)
The study investigated and determined the extent and pattern of invasion by the exotic woody species, their dispersal mechanism as well as the most successful invaders and why certain areas may be prone to invasion by exotics than others in the University Estate. This was with a view to understanding the patterns and rates of invasion of natural forest by exotic species.